2018
DOI: 10.31729/jnma.3630
|View full text |Cite
|
Sign up to set email alerts
|

Health Problems while Working as a Volunteer or Humanitarian Aid Worker in Post-Earthquake Nepal

Abstract: Introduction: Volunteers and humanitarian aid workers working in disaster struck areas of the world are a vulnerable group of travelers. Nepal saw an influx of these humanitarian aid workers following earthquakes in April and May 2015.  Methods: This was a descriptive cross-sectional study conducted at CIWEC Hospital located in Kathmandu. A questionnaire was given to all volunteers and aid workers who arrived at the hospital for evaluation of health related problems and agreed to be part of the study.&#x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Nurthen and Jung [ 22 ] reported on fatalities in the Peace Corps during 1986–2003; the major cause of death was unintentional injury (67%), and half of these injuries were caused by motor vehicle accidents. Another study of health problems in a group of volunteers or humanitarian aid workers in post-earthquake Nepal showed that 53 (56%) had gastrointestinal illness, 14 (15%) had skin diseases, and 7 (8%) had injury/musculoskeletal problems [ 23 ]. However, these issues were rarely mentioned in the full-scale exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Nurthen and Jung [ 22 ] reported on fatalities in the Peace Corps during 1986–2003; the major cause of death was unintentional injury (67%), and half of these injuries were caused by motor vehicle accidents. Another study of health problems in a group of volunteers or humanitarian aid workers in post-earthquake Nepal showed that 53 (56%) had gastrointestinal illness, 14 (15%) had skin diseases, and 7 (8%) had injury/musculoskeletal problems [ 23 ]. However, these issues were rarely mentioned in the full-scale exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Upper respiratory tract infections were observed quite frequently in the short-term period after disasters induced by earthquakes generated in several continents, including North America (the 1994 Northridge [ 68 , 69 ], 2001 El Salvador [ 70 , 71 ], and 2010 Haiti earthquakes [ 72 , 73 , 74 , 75 , 76 , 77 ], Europe (the 2009 L’Aquila earthquake [ 78 ] and 2014 Cephalonia Island earthquakes [ 79 ]), and Asia (the 1995 Kobe [ 80 ], 1999 Chi-Chi [ 81 , 82 ], 2003 Bam [ 83 , 84 ], 2004 Sumatra-Andaman [ 85 ], 2005 Kashmir [ 86 , 87 ], 2009 Sumatra [ 88 ], 2009 Samoa [ 85 ], 2011 Tōhoku [ 85 , 89 ], 2013 Lushan [ 90 , 91 ], 2013 Bohol [ 92 , 93 ], 2015 Gorkha [ 94 , 95 , 96 , 97 , 98 , 99 ] and 2016 Kumamoto earthquakes [ 100 ]) ( Figure 2 ). Most of the earthquake-affected people lived in overcrowded evacuation shelters, with inadequate air ventilation, unsafe drinking water, and poor personal hygiene being among the possible predisposing factors of contracting respiratory infectious diseases [ 70 , 71 , 72 , 80 , 81 , 82 ,…”
Section: Earthquake-triggered Respiratory Infectious Diseasesmentioning
confidence: 99%
“…Common problems recorded among volunteers included traveler’s diarrhea and skin problems. It was found that the volunteers were not adequately prepared for the situations they were likely to face, suggesting that proper information and advice on health issues before acting to the affected area can help reduce the incidence of health problems among this particular group [ 97 ]. An assessment of morbidity among Israeli rescue team personnel in Nepal after the earthquake revealed that gastrointestinal complaints were by far the most common and significant morbidity (accompanied by diarrhea 44%, vomiting 22%, and fever 10%), followed by respiratory problems (16%) [ 94 ].…”
Section: Earthquake-triggered Gastrointestinal Diseases (Water- and F...mentioning
confidence: 99%